‘Loud’ and ‘quiet’ politics: Questioning the role of ‘the artist’ in street art projects after the 2011 Egyptian Revolution - Sprengel, D (SAGE Publications, 2019)
This article examines the grassroots artistic initiative al-Fann Midan (Art is a City Square) in Cairo and a contrasting approach to street art organizing in Alexandria to demonstrate how each enacted a different relationship to ‘the political’ in a revolutionary moment. Extending sociologist Asef Bayat’s concept ‘quiet encroachment’, it analyzes these contrasting approaches through the sonic metaphor of ‘loud’ and ‘quiet’ politics. As a spectrum, this framework highlights how the everyday, the gestural, and the affective on the one hand can exist simultaneously, and at times in tension with, larger, more representational political expressions on the other. It thus avoids fetishizing creative ‘resistance’ or ‘dissent’, while nonetheless analyzing art in a revolutionary moment, by grounding creative expression more historically and with analytical attention to how it reanimates long-standing debates among Arab intellectuals regarding the role of the ‘artist’.